AN OVERVIEW OF THE TRADITIONAL USES, PHYTOCHEMICAL CONSTITUENTS, PHARMACOLOGICAL AND TOXICOLOGICAL ASPECTS OF PERSICARIA HYDROPIPER (L.) DELARBRE - OJAH, ANJUMANI; BORTHAKUR, MRIDUL KR.; KALITA, JOGEN CH. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Persicaria hydropiper (L.) Delarbre, an annual herb of the family polygonaceae, locally known as Patharua bihalagani in Assam (India), is reported as a traditional drug for birth control used by women in some parts of Assam. The current study presents the taxonomical description, geographical distribution, traditional uses, phytochemical composition, pharmacological and toxicological activities of P. hydropiper. The whole plant or part(s) like leaves, stems root etc have been traditionally used as herbal medicine for treatment of various ailments. Several bioactive components such as flavonoids, phenylpropanoids, essential oils, glycosides, phytosterols and sesquiterpenes among others were reported. The extracts and phytoconstituents of P. hydropiper possess antioxidant, anti-microbial, anti-inflammatory, cytotoxic, estrogenic, antifertility, neuroprotective activities, etc. Mutagenic activity and acute toxicity of P. hydropiper were also reported.